A bulk antistatic polyetherimide polymer and preparation method thereof
By introducing amino-terminated aniline trimers into the polyetherimide material, a conductive path is formed, which solves the problem of electrostatic hazards of polyetherimide materials, and comprehensively improves the antistatic effect and performance.
Patent Information
- Application Number
- CN202310249710.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-03-15
AI Technical Summary
The prior art is difficult to use polyaniline to achieve the body conduction of polyetherimide materials, resulting in high surface resistivity and unable to effectively reduce static hazards.
By copolymerizing the amino-terminated aniline trimer with dianhydride and diamine in an organic solvent or solid organic acid, a doped aniline trimer is formed and introduced into the polyetherimide molecule to form an effective Conductive paths, anti-static polyetherimide films are prepared by solution processing and organic acid doping methods.
The body antistatic effect of polyetherimide material is achieved, the surface and volume resistivity are reduced, and excellent mechanical properties, heat resistance and dielectric properties are maintained.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004127398960000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a novel antistatic polyetherimide polymer and a preparation method thereof. Background Art
[0002] Polyetherimide (PEI) material is obtained by introducing ether bonds into the main chain of polyimide. Therefore, PEI combines the high heat resistance, high strength, high insulation, and low dielectric loss properties of polyimide (PI) with the excellent processing properties of thermoplastic engineering plastics, becoming a high-performance engineering plastic with excellent comprehensive properties. It is widely used in electronics, machinery, automobiles, aviation and other fields.
[0003] As a low dielectric insulating material, polyetherimide can generate a large electrostatic potential by the accumulation of a small amount of static charge, thereby generating electrostatic discharge, which can cause electronic components to be broken down, damaged, or even cause accidents such as combustion and explosion, resulting in unpredictable losses. Therefore, how to eliminate the electrostatic hazards of high-performance PEI materials has been one of the important technical topics that people have been exploring for many years.
[0004] The essence of eliminating the hazards of static electricity in materials is to conduct away the static charge on the surface and prevent it from accumulating. There are two ways to conduct away the charge: one is surface conduction, and the other is bulk conduction. The surface conduction route is such as coating metal particle conductive paint or other antistatic agents, but its fatal disadvantage is that it is not durable, because both the paint and the conductive film will fall off easily, which will cause the failure of the antistatic modification. The method of bulk conduction is to add some metals, inorganic or conductive polymers to PEI materials to form antistatic materials. Conductive fillers form a conductive path in the PEI matrix material, so that the charge can leak smoothly through the conductive path to achieve the purpose of bulk conduction.
[0005] As a typical conductive polymer, polyaniline has the characteristics of low cost, easy synthesis and stable performance. The molecular structure of polyaniline is composed of a reduced benzene structure and an oxidized quinone structure. When the oxidized state and the reduced state exist at the same time, it is called a doped state. The doped polyaniline has good conductivity, and its conductivity can even be comparable to that of metals. However, the molecular chain of polyaniline is too regular and rigid, and it is difficult to dissolve in organic solvents, making it difficult to achieve bulk conduction. Summary of the invention
[0006] The purpose of the present invention is to provide a novel antistatic polyetherimide copolymer film and a preparation method thereof, so as to solve the problem that it is difficult to realize bulk conduction using polyaniline in the prior art, thereby reducing its surface resistivity and realizing antistatic modification.
[0007] To achieve the above object, the present invention provides a bulk antistatic polyetherimide polymer having a structure shown in Formula I:
[0008]
[0009] in
[0010]
[0011]
[0012] The present invention provides a method for preparing the bulk antistatic polyetherimide polymer, comprising copolymerizing dianhydride, diamine and amino-terminated aniline oligomer in an organic solvent or solid organic acid, performing a dehydration cyclization imidization reaction, and then precipitating, washing, Soxhlet extraction and drying to obtain the polymer;
[0013] The aniline oligomer is an aniline trimer.
[0014] Preferably, the preparation method of the amino-terminated aniline trimer comprises: polymerizing aniline in a protonic acid system under the action of a capping agent and an oxidant, and then reducing it with a reducing agent to obtain the amino-terminated aniline trimer; the amino-terminated aniline trimer has a structure shown in Formula II:
[0015]
[0016] Preferably, the end-capping agent is p-phenylenediamine, and the molar ratio of the end-capping agent to the aniline monomer is 1:1-3; the oxidizing agent is ammonium persulfate, and the molar ratio of the end-capping agent to the aniline monomer is 1:1.5-3; the protonic acid includes an aqueous HCl solution or an aqueous H2SO4 solution; the reducing agent includes hydrazine hydrate or zinc powder, the polymerization reaction temperature is -5-5°C, and the reaction time is 8-24h.
[0017] Preferably, the molar ratio of the amount of diamine to the amino-terminated aniline trimer is 1:0.1-0.25, and the amount of dianhydride is the sum of the molar amounts of the diamine and the amino-terminated aniline trimer.
[0018] Preferably, the dianhydride is one of bisphenol A type diether dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic acid dianhydride, and 3,3'-(m-phenylene) diether dianhydride; the diamine is one of 4,4'-diaminodiphenyl ether, 4,4'-methylenedianiline, 4,4'-diaminobiphenyl, p-phenylenediamine, and m-phenylenediamine; the solution system of the copolymerization reaction includes N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, m-cresol or solid organic acid, and the solid organic acid includes one or more of benzoic acid and salicylic acid.
[0019] Preferably, the reaction temperature of the copolymerization reaction is 15 to 35° C., the reaction time is 8 to 24 hours, and a polyamic acid solution is obtained;
[0020] The dehydration cyclization imidization reaction conditions are 200-250° C., 2-5 h;
[0021] The precipitant used in the precipitation is one of methanol, ethanol and deionized water; the extractant used in the Soxhlet extraction includes ethanol, and the condition is to perform the Soxhlet extraction at 100-150° C. for 24-48 hours.
[0022] The invention provides a method for preparing an antistatic polyetherimide film, comprising the following steps: adding the antistatic polyetherimide copolymer into an organic solvent to dissolve it, doping it with an organic acid, casting it into a film, and heating it to remove the solvent to obtain the film.
[0023] Preferably, the organic solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and m-cresol, and the solution mass concentration is 10-15%; the organic acid is dodecylbenzenesulfonic acid, and the addition amount is 2-10% of the solution volume.
[0024] Preferably, the dissolution condition is dissolving at 120-150°C; the organic acid doping method includes ultrasonic dispersion at 20-25KHz for 3-5 hours at room temperature; the method of removing the solvent by heating includes heating at 50°C for 3 hours, heating at 70°C for 1 hour, heating at 100°C for 1 hour, heating at 120°C for 1 hour, heating at 150°C for 1 hour, heating at 180°C for 1 hour, heating at 200°C for 1 hour, and heating at 230°C for 3 hours in a gradient manner.
[0025] The invention provides an antistatic polyetherimide film prepared by the antistatic polyetherimide film preparation method.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention adopts aniline oligomer as a conductive polymer, can be solution processed, and has a structure and properties similar to high molecular weight polyaniline. The amino-terminated aniline oligomer has the property of two terminal amino groups and can be used as a diamine monomer for polymerization reaction, so that the amino-terminated aniline trimer is introduced into the main chain of the polyetherimide molecule, and the doped aniline trimer forms an effective conductive path in the polyetherimide, thereby improving the antistatic effect of the polyetherimide from the path of bulk conduction, and maintaining its excellent mechanical properties (fracture stress above 40MPa), heat resistance (glass transition temperature above 200°C, carbon residue rate at 800°C above 40%) and dielectric properties (dielectric constant below 3.5 at 10GHz). DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.
[0029] The instruments, reagents, materials, etc. involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.
[0030] Example 1
[0031] Under nitrogen protection, 10.4649 g (20 mmol) of bisphenol A diether dianhydride (BPADA), 3.6798 g (18 mmol) of 4,4'-diaminodiphenyl ether and 0.5809 g (2 mmol) of amino-terminated aniline trimer and 100 ml of N-methylpyrrolidone were added to a 250 mL reaction bottle, stirred at 25 ° C for 18 h, heated to 230 ° C and refluxed for 3 h to complete the imidization reaction, and the reaction solution was added dropwise to excess methanol to precipitate, filtered, and the filter cake was washed with methanol three times. Soxhlet extraction was carried out at 130 ° C for 24 h with ethanol as the extractant, and vacuum dried to obtain polyetherimide PEI-1 in the form of gray-black powder.
[0032] Weigh 1g of PEI-1 powder and add it to 10ml of N,N-dimethylacetamide, heat it to 120℃ to fully dissolve it, cool it down to room temperature, add 0.5ml of dodecylbenzenesulfonic acid, and ultrasonically disperse it at 20-25KHz for 3h to obtain a dark green mixed solution. The obtained solution was coated on a stainless steel substrate with a diameter of 100mm and a thickness of 3mm, and the temperature was increased at 50℃-3h, 70℃-1h, 100℃-1h, 120℃-1h, 150℃-1h, 180℃-1h, 200℃-1h, 230℃-3h, 280℃-1h, and 320℃-1h to remove the solvent and excess dodecylbenzenesulfonic acid. After cooling to room temperature, the PEI-1 film was removed by film removal.
[0033] Example 2
[0034] The feed in Example 1 was changed to 9.4190 g (18 mmol) of bisphenol A diether dianhydride, 3.2699 g (16 mmol) of 4,4'-diaminodiphenyl ether and 0.5819 g (2 mmol) of amino-terminated aniline trimer, and 90 ml of N-methylpyrrolidone were added to a 250 mL reaction bottle protected by nitrogen, and other conditions remained unchanged to obtain polyetherimide PEI-2 in the form of gray-black powder.
[0035] 1 g of PEI-2 powder was weighed, and a solution was prepared and coated according to Example 1 to obtain a PEI-2 film.
[0036] Example 3
[0037] The feed in Example 1 was changed to 8.3705 g (16 mmol) of bisphenol A diether dianhydride, 2.8616 g (14 mmol) of 4,4'-diaminodiphenyl ether and 0.5812 g (2 mmol) of amino-terminated aniline trimer and 80 ml of N-methylpyrrolidone were added to a 250 mL reaction bottle, while other conditions remained unchanged to obtain polyetherimide PEI-3 in the form of gray-black powder.
[0038] 1 g of PEI-3 powder was weighed, and a solution was prepared and coated according to Example 1 to obtain a PEI-3 film.
[0039] Example 4
[0040] The feed in Example 1 was changed to 7.3260 g (14 mmol) of bisphenol A diether dianhydride, 2.5298 g (12 mmol) of 4,4'-diaminodiphenyl ether and 0.5835 g (2 mmol) of amino-terminated aniline trimer and 70 ml of N-methylpyrrolidone were added to a 150 mL reaction bottle, while other conditions remained unchanged to obtain polyetherimide PEI-4 in the form of gray-black powder.
[0041] 1 g of PEI-4 powder was weighed, and a solution was prepared and coated according to Example 1 to obtain a PEI-4 film.
[0042] Example 5
[0043] The feed in Example 1 was changed to 6.2807 g (12 mmol) of bisphenol A diether dianhydride, 2.0463 g (10 mmol) of 4,4'-diaminodiphenyl ether and 0.5820 g (2 mmol) of amino-terminated aniline trimer and 60 ml of N-methylpyrrolidone added to a 150 mL reaction bottle, while other conditions remained unchanged to obtain polyetherimide PEI-5 in the form of gray-black powder.
[0044] 1 g of PEI-5 powder was weighed, and a solution was prepared and coated according to Example 1 to obtain a PEI-5 film.
[0045] Example 6
[0046] The feed in Example 1 was changed to 5.2321 g (10 mmol) of bisphenol A diether dianhydride, 1.6375 g (8 mmol) of 4,4'-diaminodiphenyl ether and 0.5809 g (2 mmol) of amino-terminated aniline trimer and 50 ml of N-methylpyrrolidone were added to a 150 mL reaction bottle, while other conditions remained unchanged to obtain polyetherimide PEI-6 in the form of gray-black powder.
[0047] 1 g of PEI-6 powder was weighed, and a solution was prepared and coated according to Example 1 to obtain a PEI-6 film.
[0048] Example 7
[0049] Under nitrogen protection, 3.1259g (6mmol) of bisphenol A type diether dianhydride, 1.0944g (5.4mmol) of 4,4'-diaminodiphenyl ether, 0.1735g (0.6mmol) of amino-terminated aniline trimer, and 25g of salicylic acid, which were mixed in advance, were added to a 100ml reaction bottle, and placed in an oil bath pot preheated to 170°C to melt salicylic acid. After it was completely melted, it was stirred and reacted for 1.5h. The reaction solution was poured onto aluminum foil while hot, and the solid was removed after it cooled to room temperature. The solid was crushed with a pulverizer, and the salicylic acid was washed off with excess methanol. Then, ethanol was used as an extractant and refluxed at 130°C for 24h for Soxhlet extraction, and vacuum dried to obtain polyetherimide PEI-7 in the form of gray-black powder.
[0050] Weigh 1g of PEI-7 powder and add it to 10ml of N,N-dimethylacetamide, heat it to 120℃ to fully dissolve it, then add 0.5ml of dodecylbenzenesulfonic acid and ultrasonically disperse it for 3h after cooling to room temperature to obtain a dark green mixed solution. The obtained solution was coated on a stainless steel substrate with a diameter of 100mm and a thickness of 3mm, and the temperature was increased at 50℃-3h; 70℃-1h; 100℃-1h; 120℃-1h; 150℃-1h; 180℃-1h; 200℃-1h; 230℃-3h, 280℃-1h, and 320℃-1h to remove the solvent and excess dodecylbenzenesulfonic acid. After cooling to room temperature, the PEI-7 film was removed by film removal.
[0051] Example 8
[0052] The feed in Example 7 was changed to 2.3540 g (4.5 mmol) of bisphenol A diether dianhydride, 0.8190 g (4 mmol) of 4,4'-diaminodiphenyl ether and 0.1463 g (0.5 mmol) of amino-terminated aniline trimer and 19 g of salicylic acid which were mixed in advance and added into a 100 ml reaction bottle, while other conditions remained unchanged, to obtain polyetherimide PEI-8 in the form of gray-black powder.
[0053] 1 g of PEI-8 powder was weighed, and a solution was prepared and coated according to Example 7 to obtain a PEI-8 film.
[0054] Example 9
[0055] The feed in Example 7 was changed to 2.0942 g (4 mmol) of bisphenol A diether dianhydride, 0.7159 g (3.5 mmol) of 4,4'-diaminodiphenyl ether and 0.1468 g (0.5 mmol) of amino-terminated aniline trimer and 17 g of salicylic acid which were mixed in advance and added into a 100 ml reaction bottle, while other conditions remained unchanged to obtain polyetherimide PEI-9 in the form of gray-black powder.
[0056] 1 g of PEI-9 powder was weighed, and a solution was prepared and coated according to Example 7 to obtain a PEI-9 film.
[0057] Example 10
[0058] The feed in Example 7 was changed to 3.6617 g (7 mmol) of bisphenol A diether dianhydride, 1.2289 g (6 mmol) of 4,4'-diaminodiphenyl ether and 0.2913 g (1 mmol) of amino-terminated aniline trimer and 30 g of salicylic acid which were mixed in advance and added into a 100 ml reaction bottle, while other conditions remained unchanged, to obtain polyetherimide PEI-10 in the form of gray-black powder.
[0059] 1 g of PEI-10 powder was weighed, and a solution was prepared and coated according to Example 7 to obtain a PEI-10 film.
[0060] Embodiment 11
[0061] The feed in Example 7 was changed to 3.1397 g (6 mmol) of bisphenol A diether dianhydride, 1.0220 g (5 mmol) of 4,4'-diaminodiphenyl ether and 0.2928 g (1 mmol) of amino-terminated aniline trimer and 25 g of salicylic acid which were mixed in advance and added into a 100 ml reaction bottle, while other conditions remained unchanged, to obtain polyetherimide PEI-11 in the form of gray-black powder.
[0062] 1 g of PEI-11 powder was weighed, and a solution was prepared and coated according to Example 7 to obtain a PEI-11 film.
[0063] Example 12
[0064] The feed in Example 7 was changed to 2.6184 g (5 mmol) of bisphenol A diether dianhydride, 0.8179 g (4 mmol) of 4,4'-diaminodiphenyl ether and 0.2912 g (1 mmol) of amino-terminated aniline trimer and 21 g of salicylic acid which were mixed in advance and added into a 100 ml reaction bottle, while other conditions remained unchanged, to obtain polyetherimide PEI-12 in the form of gray-black powder.
[0065] Weigh 1 g of PEI-12 powder, prepare a solution and apply film according to Example 7 to obtain a PEI-12 film.
[0066] Examples 7 to 12 were respectively carried out under the same experimental conditions with the solvent systems changed in Examples 1 to 6. Examples 1 to 6 were NMP systems, and Examples 7 to 12 were salicylic acid systems. The products obtained were characterized by NMR infrared and had the same structure; however, the molecules of the products obtained in Examples 7 to 12 were more tightly arranged, so the solubility was relatively low, and concentrated solutions could not be prepared to prepare thin films, so subsequent thin film tests were all carried out using Examples 1 to 6.
[0067] The reaction formula in Examples 1 to 12 is shown in Formula III:
[0068]
[0069] Comparative Example 1: No aniline trimer or dodecylbenzene sulfonic acid was added
[0070] Under nitrogen protection, 13.0880 g (25 mmol) of bisphenol A diether dianhydride, 5.1086 g (25 mmol) of 4,4'-diaminodiphenyl ether and 120 ml of N-methylpyrrolidone were added to a 250 mL reaction bottle, stirred at 25 ° C for 18 h, heated to 230 ° C and refluxed for 3 h to complete the imidization reaction, and the reaction solution was added dropwise to excess methanol to precipitate, filtered, and the filter cake was washed with methanol three times. Soxhlet extraction was carried out at 130 ° C for 24 h with ethanol as the extractant, and vacuum dried to obtain polyetherimide PEI-0 in the form of light yellow powder.
[0071] Weigh 1g of PEI-0 powder and add it to 10ml of N,N-dimethylacetamide, heat it to 120℃ to fully dissolve it, and then cool it to room temperature to obtain a light yellow transparent solution. The obtained solution is coated on a stainless steel substrate with a diameter of 100mm and a thickness of 3mm, and the solvent is removed by heating at 50℃-3h, 70℃-1h, 100℃-1h, 120℃-1h, 150℃-1h, 180℃-1h, 200℃-1h, 230℃-3h, 280℃-1h, and 320℃-1h. After cooling to room temperature, remove the film to obtain a PEI-0 film.
[0072] The reaction formula in Comparative Example 1 is shown in Formula IV:
[0073]
[0074] Comparative Example 2: No aniline trimer was added, only dodecylbenzene sulfonic acid was added
[0075] Weigh 1g of PEI-0 powder, add it to 10ml of N,N-dimethylacetamide and heat it to 120℃ to fully dissolve it. After cooling to room temperature, add 0.5ml of dodecylbenzenesulfonic acid and ultrasonically disperse it for 3h to obtain a light yellow transparent mixed solution. The obtained solution was coated on a stainless steel substrate with a diameter of 100mm and a thickness of 3mm, and the temperature was increased at 50℃-3h, 70℃-1h, 100℃-1h, 120℃-1h, 150℃-1h, 180℃-1h, 200℃-1h, 230℃-3h, 280℃-1h, and 320℃-1h to remove the solvent and dodecylbenzenesulfonic acid. After cooling to room temperature, the PEI-0' film was removed by demolding.
[0076] Comparative Example 3
[0077] Weigh 0.5 g of amino-terminated aniline trimer into a 100 ml round-bottom flask, disperse it in 20 ml of deionized water, add 3 ml of dodecylbenzenesulfonic acid and ultrasonically disperse it for 3 hours to fully dope it, filter it, and wash it with deionized water to obtain the doped aniline trimer in the form of black powder.
[0078] Weigh 1g of PEI-0 powder and 0.0413g of doped aniline trimer, add them to 10ml of N,N-dimethylacetamide, heat to 120℃ for full dissolution, and cool to room temperature. The resulting solution is coated on a stainless steel substrate with a diameter of 100mm and a thickness of 3mm, and the temperature is increased at 50℃-3h; 70℃-1h; 100℃-1h; 120℃-1h; 150℃-1h; 180℃-1h; 200℃-1h; 230℃-3h, 280℃-1h, and 320℃-1h to remove the solvent. After cooling to room temperature, remove the film to obtain PEI-1' film.
[0079] Comparative Example 4
[0080] Weigh 1g of PEI-0 powder and 0.0461g of doped aniline trimer, add them into 10ml of N,N-dimethylacetamide, heat to 120°C to fully dissolve, and cool to room temperature. Coating and heating are performed according to Comparative Example 3 to obtain a PEI-2' film.
[0081] Comparative Example 5
[0082] Weigh 1g of PEI-0 powder and 0.0522g of doped aniline trimer, add them into 10ml of N,N-dimethylacetamide, heat to 120°C to fully dissolve, and cool to room temperature. Coating and heating are performed according to Comparative Example 3 to obtain a PEI-3' film.
[0083] Comparative Example 6
[0084] Weigh 1g of PEI-0 powder and 0.0598g of doped aniline trimer, add them into 10ml of N,N-dimethylacetamide, heat to 120°C to fully dissolve, and cool to room temperature. Coating and heating are performed according to Comparative Example 3 to obtain a PEI-4' film.
[0085] Comparative Example 7
[0086] Weigh 1g of PEI-0 powder and 0.0704g of doped aniline trimer, add them into 10ml of N,N-dimethylacetamide, heat to 120°C to fully dissolve, and cool to room temperature. Coating and heating are performed according to Comparative Example 3 to obtain a PEI-5' film.
[0087] Comparative Example 8
[0088] Weigh 1g of PEI-0 powder and 0.0853g of doped aniline trimer, add them into 10ml of N,N-dimethylacetamide, heat to 120°C to fully dissolve, and cool to room temperature. Coating and heating are performed according to Comparative Example 3 to obtain a PEI-6' film.
[0089] The structures of Examples 1 to 12 were characterized by nuclear magnetic resonance and infrared absorption spectra, verifying that the structures of the products were in line with expectations. However, since the reactions of Examples 7 to 12 were carried out in a solid organic acid system, the resulting polymer molecular chains were densely stacked and had low solubility in organic solvents, making it difficult to prepare concentrated solutions for film preparation. However, the structures of Examples 7 to 12 corresponded to the structures of Examples 1 to 6, respectively, and the products of Examples 1 to 6 were used in subsequent film preparation.
[0090] The polyetherimide films obtained in Examples 1 to 6 and Comparative Examples 1 to 8 were tested for surface resistivity, and the results are shown in Table 1. The surface resistivity test was performed using a ZST121 volume surface resistivity tester produced by Beijing Aerospace Zongheng Testing Instrument Co., Ltd., with a charging voltage of 500V.
[0091]
[0092] Table 1. Test results of polyetherimide films obtained in the examples and comparative examples
[0093] Comparative Examples 3 to 8 are physically blended films prepared at the same proportions as Examples 1 to 6. From the experimental data in the above table, it can be seen that compared with the PEI films without adding aniline trimer in Comparative Examples 1 and 2 and the physically blended composite films in Comparative Examples 3 to 8, the surface resistivity of the polyetherimide copolymer films prepared in Examples 1 to 6 of the present invention is reduced by 7 to 9 orders of magnitude, and with the increase of aniline trimer structural units, the surface and volume resistivities of the obtained copolymer films are lower, meeting the requirements for bulk antistatic, among which Example 6 has the most obvious effect of reducing the surface and volume resistivities.
[0094] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A bulk antistatic polyetherimide polymer, characterized in that: It has the structure shown in formula I: The preparation method of the bulk antistatic polyetherimide polymer comprises copolymerizing dianhydride, diamine and amino-terminated aniline oligomer in an organic solvent or solid organic acid, performing dehydration cyclization imidization reaction, and then precipitating, washing, Soxhlet extraction and drying to obtain the polymer; The aniline oligomer is an aniline trimer; The diamine is 4,4'-diaminodiphenyl ether; The molar ratio of the amount of diamine to the amino-terminated aniline trimer is 1:0.2-0.25, and the amount of dianhydride is the sum of the molar amounts of the diamine and the amino-terminated aniline trimer; The dianhydride is bisphenol A type diether dianhydride; The solid organic acid includes one or more of benzoic acid and salicylic acid; The reaction temperature of the copolymerization reaction is 15-35° C., and the reaction time is 8-24 hours to obtain a polyamic acid solution; The dehydration cyclization imidization reaction conditions are 200-250° C., 2-5 h; The precipitant used in the precipitation is one of methanol, ethanol and deionized water; the extractant used in the Soxhlet extraction includes ethanol, and the condition is to perform the Soxhlet extraction at 100-150° C. for 24-48 hours.
2. The method for preparing the bulk antistatic polyetherimide polymer according to claim 1, characterized in that: The preparation method of the amino-terminated aniline trimer comprises: polymerizing aniline in a protonic acid system under the action of a capping agent and an oxidant, and then reducing it with a reducing agent to obtain the amino-terminated aniline trimer; the amino-terminated aniline trimer has a structure shown in formula II: 。 3. The method for preparing the bulk antistatic polyetherimide polymer according to claim 2, characterized in that: The end-capping agent is p-phenylenediamine, and the molar ratio of the end-capping agent to the aniline monomer is 1:1-3; the oxidizing agent is ammonium persulfate, and the molar ratio of the end-capping agent to the aniline monomer is 1:1.5-3; the protonic acid includes an aqueous HCl solution or an aqueous H2SO4 solution; the reducing agent includes hydrazine hydrate or zinc powder, the polymerization reaction temperature is -5-5°C, and the reaction time is 8-24h.
4. The method for preparing the bulk antistatic polyetherimide polymer according to claim 1, characterized in that: The solution system for the copolymerization reaction includes N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, m-cresol or solid organic acid.
5. A method for preparing an antistatic polyetherimide film, characterized in that: The following steps are involved: The bulk antistatic polyetherimide polymer as claimed in any one of claims 1 to 4 is added into an organic solvent to dissolve, then doped with an organic acid, cast into a film, and heated to remove the solvent to obtain the film.
6. The method for preparing the antistatic polyetherimide film according to claim 5, characterized in that: The organic solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and m-cresol, and the mass concentration of the solution is 10-15%; the organic acid is dodecylbenzenesulfonic acid, and the addition amount is 2-10% of the volume of the solution; the dissolution condition is dissolving at 120-150° C.; the method of doping with the organic acid includes ultrasonic dispersion at room temperature and 20-25 kHz for 3-5 hours; The method for removing the solvent by increasing the temperature comprises increasing the temperature in a gradient manner by heating at 50°C for 3 hours, heating at 70°C for 1 hour, heating at 100°C for 1 hour, heating at 120°C for 1 hour, heating at 150°C for 1 hour, heating at 180°C for 1 hour, heating at 200°C for 1 hour, and heating at 230°C for 3 hours.
7. The antistatic polyetherimide film prepared by the method for preparing an antistatic polyetherimide film according to any one of claims 5 to 6.
Citation Information
Patent Citations
Synthetic method of polyaniline nanofiber with helical structure
CN104098770A
One-step method for preparing polyimide by taking organic aromatic acid as reaction medium
CN113912848A
Diamine having oligo-aniline unit and polyimide
JP2000044683A